Development of a Budikdamber System in Fulfilling Family Food Security: Pengembangan Sistem Budikdamber Dalam Pemenuhan Ketahanan Pangan Keluarga - Ahya Kamilah; Ridwan Lutfiadi; Nana Danapriatna; m ikhwan rahmanto; Ismarani .; Haris Budiyono (Fakultas Teknologi dan Industri Pangan Unisri Surakarta, 2024)
This training in agriculture was carried out based on problems in urban areas. The problems was limited land and capital. Beside that its called as efforts to fulfill urban society's nutrition. The training conducted was fish farming in a bucket or in Indonesian it is called Budikdamber. The training was held in Sindangmulya Village, Cibarusah District, Bekasi Regency with the target participants were housewives. The results showed that all participants, namely the Dahlia Farmer Women's Group (KWT) were very active and responded well. Evidenced by their enthusiasm in participating in the counseling process, as well as the Budikdamber practicum. The harvest can fulfill family nutrition and increase income. This program can achieve the desired target because it has a good impact on KWT members who are equipped with knowledge and skills.